2019
DOI: 10.26499/mab.v7i2.175
|View full text |Cite
|
Sign up to set email alerts
|

Disfemisme Pada Wacana Lingkungan: Sebuah Kajian Ekolinguistik Kritis Dalam Media Massa Di Indonesia

Abstract: Media massa menggunakan berbagai piranti bahasa untuk mengemas ideologi konstruktif dan destruktif terkait dengan lingkungan, misalnya eufemisme dan disfemisme. Penelitian ini berusaha mengkaji permasalahan kebahasaan yang terdapat dalam wacana lingkungan dalam media massa di Indonesia, yakni mengenai disfemisme. Penelitian ini merupakan penelitian deskriptif kualitatif. Data dikumpulkan dari majalah Gatra, Tempo, Trust, harian Kompas, Kabar Indonesia, Media Indonesia, Suara Merdeka, dan Surabaya Pagi, portal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
6
0
4
Order By: Relevance
“…These finding has a significant different with the previous studies. In Elisa's research, she found 13 functions of euphemism and 12 functions of dysphemism in general news of environmental discourse [10]. In Elisa's research, there are 3 functions of euphemism found in the general news of environmental discourse [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These finding has a significant different with the previous studies. In Elisa's research, she found 13 functions of euphemism and 12 functions of dysphemism in general news of environmental discourse [10]. In Elisa's research, there are 3 functions of euphemism found in the general news of environmental discourse [3].…”
Section: Discussionmentioning
confidence: 99%
“…This study used printed newspaper and online newspaper from Indonesia media which are Gatra, majalah Tempo, majalah Trust, harian Kompas, harian Kabar Indonesia, harian Media Indonesia, harian Suara Merdeka, and harian Surabaya Pagi. Meanwhile, online newspaper was taken from Antara, Vivanews, Detiknews, Metronews, dan Okezone [10]. Those data were chosen because the researcher concern on mainstream media which is the popular reference for audiences.…”
Section: Introductionmentioning
confidence: 99%
“…Kurniawati (2011) gives reasons other than those mentioned above: (10) to cover up shame; (11) to show oneself as an educated person; (12) relating to religion or belief. Laili (2012) Previous research on euphemisms done by Kurniawati (2011), Laili (2016), Sariah (2017), Fadely (2017), and Heryana (2019). In previous studies, the form of euphemism research was in the form of grammatical units.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the research on the linkage of environmental reporting to mass media by Laili (2012) entitled "Euphemism and Dysphemism on Environmental Discourse: a Critical Ecolinguistics Study in Mass Media in Indonesia". The research examines language problems contained in the environmental discourse in the mass media in Indonesia which is about euphemism and dysphemism.…”
Section: Introductionmentioning
confidence: 99%